Reprodução e crescimento de minhocas e biomassa microbiana em substratos - Morais, Francimar Maik da Silva (Universidade Federal Rural do Semi-Árido, 2019)
The humus produced during earthworm vermicomposting has been excellent for acting physicochemical and biological attributes soil. Within biological attributes, substrates have different actions on earthworm growth and reproduction, and soil microbial biomass. Thus, the objective of this work was to evaluate the influence of substrates with different proportions of residues of plant and animal origin on the reproduction and growth of earthworms (Eisenia foetida), as well as, to analyze their effect on soil microbial biomass carbon at semi-arid region from Rio Grande do Norte states, Brazil. The experiment was carried out together with the farmers belonging to the Agrovila Pomar Family Farmers Association, on the MAISA farm, in the municipality of Mossoró-RN. The experimental design was a randomized block design, in 6 x 4 factorial scheme with four repetitions. The treatments consisted of six substrates: T1 - Cattle manure + Cashew tree leaves (Anacardium occidentale L.); T2 - Goat manure + Cashew tree leaves; T3- Cattle manure + Catanduva tree leaves (Piptadenia moniliformis Benth.); T4 - Goat manure + Catanduva tree leaves; T5 - Cattle manure + Cashew tree leaves + Catanduva tree leaves; T6- Goat manure + Cashew tree leaves + Catanduva tree leaves, with four evaluation dates (30, 60, 90 and 120 days), totaling 96 experimental units. For the number of worms, multiplication index and microbial biomass it was observed that the treatments T1 (41; 11; 16g), T3 (40; 10; 16g) e T5 (49; 12; 17g), respectively, were superior to the other treatments. Regardless of plant residue, cattle manure stimulated the multiplication and growth of the earthworm Eisenia foetida. Worm length was a genetic factor not stimulated by substrate type. The largest supply of carbon and energy by cattle manure for use by microorganisms, provided higher carbon content in the substrate microbial biomass. The amount of substrate consumed by earthworms was sufficient to increase earthworm growth and reproduction up to a maximum of 83 days using substrate with cattle manure.and, 72 days for goat manure substrate. There was a linear reduction of microbial biomass over 120 days of composting.
Monografia
Keywords: Vermicompostagem; Esterco bovino; Esterco caprino; Carbono da biomassa microbiana; Vermicomposting; Cattle manure; Goat manure; Carbon of microbial biomass; CIENCIAS AGRARIAS::AGRONOMIA